2000
DOI: 10.3109/07435800009048571
|View full text |Cite
|
Sign up to set email alerts
|

Hypophysectomy Results in a Loss of Connexin Gap Junction Protein from the Adrenal Cortex

Abstract: To test the hypothesis that gap junctions are dependent on the tropic state of the adrenal gland, the effect of hypophysectomy on connexin 43 (alpha1-Cx43) gap junction protein occurrence and distribution was examined in mice. Gap junction protein occurrence was assessed with immunohistochemical techniques. In the adrenal gland from intact animals, alpha1-Cx43 gap junction protein was detected in the zonae fasciculata(ZF) and reticularis (ZR) while only a few alpha1-Cx43 gap junction plaques were found connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
2
10
0
1
Order By: Relevance
“…The results presented herein corroborate those of studies reporting that hypophysectomy tends to cause atrophy of the inner zones of the adrenal cortex (Deane 1962;Tchen et al 1977;Ceccatelli et al 1995;Davis et al 2000). These observations suggest that the atrophy of the inner zones is attributable to alterations in the G1/S transition phase of the adrenal cell cycle.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The results presented herein corroborate those of studies reporting that hypophysectomy tends to cause atrophy of the inner zones of the adrenal cortex (Deane 1962;Tchen et al 1977;Ceccatelli et al 1995;Davis et al 2000). These observations suggest that the atrophy of the inner zones is attributable to alterations in the G1/S transition phase of the adrenal cell cycle.…”
Section: Discussionsupporting
confidence: 95%
“…Conversely, we have observed that the ZG of hypophysectomized rats increases in size and presents larger numbers of BrdU-positive cells. These results are in agreement with those of Nussdorfer et al (1973) and with those of Nickerson and Brownie (1975), whereas other authors have described few or no post-hypophysectomy alterations in the ZG (Deane 1962;Tchen et al 1977;Ceccatelli et al 1995;Davis et al 2000). Nussdorfer et al (1973) have reported that, by post-hypophysectomy day 7, the ZG increases significantly in width, despite absolute decreases in its volume, suggesting that a linear parameter is not a reliable measure of ZG size.…”
Section: Discussionsupporting
confidence: 93%
“…As hypothesized [21], gap junctional communication in the adrenal cortex plays a pivotal role in a number of interactive cell [8,9,13,15] Mouse ? [9,12,14,27] Guinea pig ? [9] Cow ?…”
Section: Connexin Intercellular Channelsmentioning
confidence: 99%
“…Collectively, this indicates that expression of adrenocortical gap junctions is under hormonal control. Strengthening further the evidence that adrenocortical gap junctions are hormonally regulated, is the finding that hypophysectomy leads to a decrease in Cx43 expression in the ZF and ZR, and that Cx43-mediated cell-cell communication is restored by subsequent ACTH treatment [27]. The physiological contribution of gap junction-mediated cell-cell communication to adrenocortical hormone release is demonstrated by the tissue response to low ACTH concentrations [22,28].…”
Section: Connexin Intercellular Channelsmentioning
confidence: 99%
“…However, our immunohistochemical analysis of PECAM and von Willebrand-positive cells showed that interactions between steroidogenic cells and endothelial cells in adrenal are largely dictated by proximity. Inside the adrenal cortex, the cells are linked by gap junctions (33) whose expression in the zona fasciculata is restored by ACTH treatment in hypophysectomized mice (10). Thus gap junction-mediated communication between hormone-responsive and nonresponsive cells is one mechanism for a potential paracrine communication.…”
Section: Discussionmentioning
confidence: 99%